Reconstituting public service broadcasting - Ruth Teer-Tomaselli; Keyan Tomaselli (Communicare)
As South Africa moved from formal apartheid to multi-party elections between February 1990 and April 1994, a unique testing ground for theories of media and democracy became available for analysis. Political struggles and discourses at every level of state and civil society were dominated by the demands of pressure groups, some with military support. Little agreement existed on what constituted democracy, on how such a practice could be attained, and whether or not a single nation could be forged out of the linguistic, cultural, ethnic, racial, class and geographical patchwork into which South Africa has been fragmented by apartheid.